Meningkatkan Aktivitas Belajar, Keterampilan Berpikir Kritis dan Motivasi Belajar Siswa, Menggunakan Kombinasi Model PBL, Discovery Learning dan Talking Stick - Muhamad Safwan Hadi; Metroyadi (CV. ITTC INDONESIA, 2023)
The research problem is that students have difficulty understanding the concepts being studied, students are less able to think critically, students tend to be passive and students lack motivation in monotonous learning. The purpose of this research is to find out teaching activities, student activities, increasing critical thinking and student learning motivation. This research uses the type of Classroom Action Research (CAR), which is carried out using four meetings. The research subjects were fifth grade students at Sungai Miai 8 Public Elementary School, Central Banjarmasin District, Banjarmasin City for the 2022/2023 academic year. what will happen this research shows that research in meetings I to IV increases. based on these findings it can be concluded that the combination of Problem Based Learning, Discovery Learning and Talking Stick models can improve teaching activities, critical thinking, student learning motivation, student activities.